Knowledge and Family Support in Nutritional Management of Productive Age Hemodialysis Patients - Esi Afriyanti; Boby Febri Krisdianto; Chichi Hafifa Transyah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: End-stage renal disease (ESRD) is a condition of total kidney failure whose prevalence continues to increase, mainly affecting productive age groups who contribute significantly to the family and country's economy. ESRD patients generally undergo hemodialysis, which causes high-cost burdens and significant changes in life due to physical impacts, absence from work, and effects of therapy. Quality and compliance with hemodialysis, including nutrition and fluid management, are essential because non-compliance can lead to decreased productivity, increased morbidity, and patient mortality. Optimal nutrition and fluid management require support and knowledge from the family. This study aimed to analyze the interaction of family knowledge and support with nutrition and fluid management in hemodialysis patients as measured by the results of clinical laboratory examinations in the productive age group. Methods: This study used a quantitative approach with a cross-sectional survey design involving 191 hemodialysis patients using a purposive sampling technique with certain criteria in West Sumatra, an area known for its unique culture and dietary patterns. The study was conducted in four hemodialysis referral hospitals. The knowledge instrument was compiled based on the Kidney Disease Questionnaire and chronic kidney disease nutrition guidelines, consisting of 23 statements, and the Family Support Instrument was adapted from the Family Support Scale (FSS) with 19 statement items. Nutrition and fluid management data were collected through observation sheets based on clinical laboratory results such as urea, creatinine, albumin, sodium, potassium, and IDWG. Spearman's rank correlation analysis was used with a significance level of ?<0.05 Results: The results showed no significant relationship between knowledge and Hemoglobin, creatinine, sodium, potassium, and Interdialytic Weight Gain (IDWG) (p>0.05). However, knowledge was related to urea (p=0.037) with weak strength and a negative direction (r = -0.151). Family support was not significantly related to Hemoglobin, urea, creatinine, sodium, potassium, and IDWG levels (p>0.05). Conclusion: This study shows that knowledge is only related to urea levels, while family support has no significant effect on nutritional and fluid compliance. These findings emphasize the importance of personal education, intensive monitoring, and family involvement in supporting nutritional and fluid management in hemodialysis patients.